EDAPHIC FACTORS AFFECTING DISTRIBUTION OF SOIL FUNGI IN THREE CHOTTS LOCATED IN ALGERIAN DESERT - DENDOUGA, WASSILA; BOUREGHDA, HOUDA; BELHAMRA, MOHAMED (Courrier du Savoir, 2015)
ABSTRACT A total of 327 colonies of fungi were isolated from three chotts located in the Northeast of Algerian Sahara (Chott Merouane, Melghir and Tighdidine). Twenty eight species representing thirteen genera were recorded in Chott Merouane, twenty two species representing eleven genera were isolated from Chott Melghir and twenty five species corresponding to eleven genera were recorded in Chott Tighdidine. The most common genera were Aspergillus, Penicillium and Cladosporium. Statistical analysis revealed a significant positive correlation between fungal population and number of edaphic factors, especially organic carbon and nitrogen contents. Fungal population showed negative correlation with chloride and sodium. The most species isolated in this study were melanized fungi. KEYWORDS: Fungi, distribution, hypersaline soil, edaphic factors. RESUME Trois cent vint sept colonies de champignons filamenteux sont isolées à partir de trois chotts localisés dans le Nord-est du Sahara Algerien (Chott Merouane, Melghir and Tighdidine). Vingt-huit espèces de 13 genres ont été isolées de Chott Merouane. Vingt-deux espèces de 11 genres ont été isolées de Chott Melghir et vingt-cinq espèces correspondant à 11 genres ont été obtenues de Chott Tighdidine. Les genres les plus abondants sont Aspergillus, Penicillium et Cladosporium. L'analyse statistique a révélé une corrélation positive significative entre la densité de la population fongique et un nombre des facteurs édaphiques, en particulier la teneur en carbone organique et l’azote. La densité de la population fongique a montré une corrélation négative avec la teneur de chlorure et de sodium. MOTS CLES: Champignons filamenteux, distribution, sol hypersalin, facteurs édaphiques.